2022
DOI: 10.1088/1755-1315/951/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo as future bio-industrial material: Physical behaviour and bending strength of Malaysia’s Beting bamboo (Gigantochloa levis)

Abstract: In this paper, bending strength and physical properties (specific gravity, dimensional stability and equilibrium moisture content) of a Malaysian bamboo locally known as Beting bamboo (Gigantochloa levis) are addressed. Characterizations of physical and bending strength of G. levis in terms of the variability of location along culm height (top, middle, bottom), culm section (nodes and internodes), fiber orientation (longitudinal, tangential and radial) and culm layer (outer and inner) were conducted. Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…This is similar to the study reported by Suchart and Thaipetch ( 2004) with specific gravity of G. albociliata ranging from 0.62 to 0.68. Despite this, it has a lower specific gravity (0.74 to 0.90) than G. levis, which was studied by Osman et al (2022). Figure 1(b) shows that the number of vascular bundles increases and becomes tighter together from the bottom to the top.…”
Section: Physical Propertiesmentioning
confidence: 97%
“…This is similar to the study reported by Suchart and Thaipetch ( 2004) with specific gravity of G. albociliata ranging from 0.62 to 0.68. Despite this, it has a lower specific gravity (0.74 to 0.90) than G. levis, which was studied by Osman et al (2022). Figure 1(b) shows that the number of vascular bundles increases and becomes tighter together from the bottom to the top.…”
Section: Physical Propertiesmentioning
confidence: 97%
“…If particular natural forests are reduced, it is a great substitute for wood due to the decreasing availability of lumber and growing concern among consumers of wood manufactured commodities about the environmental impacts. Bamboo's structural, physical, and inherent resilience are changed based on a number of variables such as farming practices and heredity [27]. Guada bamboo and Moso bamboo are the two most popular species used in construction; they have the equivalent strength-to-weight ratio as steel and about double the compression-to-weight ratio of concrete, indicating their high ability to endure tremendous pressure and weight [28].…”
Section: Recycled Plasticsmentioning
confidence: 99%
“…In recent years, bamboo has gained popularity as a substitute for wood due to its rapid growth, short rotation cycle, simple cultivation methods, excellent mechanical strength, moderate to high density, straightforward processing, and versatility in various industrial applications. Additionally, the global focus on bamboo has significantly risen due to the shortage of forest resources and increased global demand for wood raw materials [ 1 , 2 ]. A viable approach for enhanced valorization of bamboo is its use for manufacturing lignin-based composites, e.g., bamboo oriented strand boards (BOSBs) [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%